2019
DOI: 10.1038/s41375-019-0446-4
|View full text |Cite
|
Sign up to set email alerts
|

Short telomeres are associated with inferior outcome, genomic complexity, and clonal evolution in chronic lymphocytic leukemia

Abstract: Telomere length in chronic lymphocytic leukemia (CLL) has been shown to be of prognostic importance, but the analyses have largely been executed on heterogeneous patient cohorts outside of clinical trials. In the present study, we performed a comprehensive analysis of telomere length associations in the well characterized CLL8 trial (n = 620) of the German CLL study group, with validation in a representative cohort of the CLL4 trial (n = 293). Absolute telomere length was

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(36 citation statements)
references
References 38 publications
1
35
0
Order By: Relevance
“…Deletion of these genes therefore permits these tumor cell clones to undergo further telomere shortening compared to non-17p-/11q-, without activating cell death pathways. In line with this, short telomere length was found to be associated with the presence of mutations in TP53 ( 37 , 40 , 41 , 43 ) and ATM ( 41 , 43 , 44 ). Cases with 17p- or TP53 mutation but long telomere length were found to have mutated IGHV ( 40 , 43 ).…”
Section: Telomere Length Associations and Prognostic Impact Of Telomesupporting
confidence: 61%
“…Deletion of these genes therefore permits these tumor cell clones to undergo further telomere shortening compared to non-17p-/11q-, without activating cell death pathways. In line with this, short telomere length was found to be associated with the presence of mutations in TP53 ( 37 , 40 , 41 , 43 ) and ATM ( 41 , 43 , 44 ). Cases with 17p- or TP53 mutation but long telomere length were found to have mutated IGHV ( 40 , 43 ).…”
Section: Telomere Length Associations and Prognostic Impact Of Telomesupporting
confidence: 61%
“…However, different telomerase activity between CD49d 2 and CD49d 1 cells can be hypothesized, 46 and that different telomere shortening may occur in follow-up samples cannot be ruled out, as it was reported in CLL cases with clonal evolution. 47 In light of all previous considerations, it was not completely unexpected that bimCD49d CLL patients, even in the presence of a small CD49d 1 subpopulation, followed a clinical outcome similar to that of homCD49d 1 patients in CLL cases treated with conventional chemoimmunotherapy. Of note, both homCD49d 1 and bimCD49d expression retained independent prognostic impact in multivariate models, which included the main clinical and biological prognosticators.…”
Section: Discussionmentioning
confidence: 84%
“…In addition, a recent paper from the German CLL Study Group found an association between short telomere length, TP53 abnormalities, early relapse after chemoimmunotherapy and adverse survival. 33 In particular, cases with 17p-or TP53 mutations had the shortest telomeres length, increase genomic complexity as well as clonal evolution. 33 The challenge of contemporary CLL treatment involves attempts to tailor therapy according to the patients' specific biological risk profile.…”
Section: Discussionmentioning
confidence: 99%
“…33 In particular, cases with 17p-or TP53 mutations had the shortest telomeres length, increase genomic complexity as well as clonal evolution. 33 The challenge of contemporary CLL treatment involves attempts to tailor therapy according to the patients' specific biological risk profile. To responsibly and effectively advance the development of new targeted therapies, novel drugs should be specifically offered to patient subgroups who can gain the greatest benefit compared with established chemoimmunotherapy strategies.…”
Section: Discussionmentioning
confidence: 99%